Assessment of Galileo E6B Data Demodulation Performance at High Latitudes: A Norwegian Vessel Case Study - Melania Susi (MDPI AG, 2021)
The Galileo High Accuracy Service (HAS) is currently in its testing phase, in which actual corrections are transmitted along with standard dummy messages. The dissemination of Precise Point Positioning (PPP) corrections is performed using an innovative scheme based on a Reed–Solomon code, which allows the reconstruction of the original navigation message from a subset of received pages. This approach introduces robustness to the reception process and aims at reducing the Time-to-Retrieve Data (TTRD); that is, the time to retrieve the HAS message. This study investigated the HAS demodulation performance considering Galileo signals collected at high latitudes. In particular, a Galileo E6-capable receiver was mounted on a vessel sailing from Bergen to Kirkenes, Norway, and reaching up to 71 degrees North. The trajectory of the vessel was at the border of the Galileo HAS service area and high-latitudes impact reception conditions, potentially leading to poor satellite geometries. Three months of data from January to March 2021 were analyzed, considering several metrics including Bit Error Rate (BER), Page Error Rate (PER), and TTRD. The analysis shows that the Reed–Solomon scheme adopted for data dissemination is also effective at high-latitudes, with daily PER below one percent and mean TTRD in the order of eight seconds when three satellites are broadcasting valid HAS corrections. Lower values of the TTRD are achieved with an increased number of satellites. These values are significantly lower than the update rate of the corrections broadcast by the Galileo HAS.